Noninvasive Monitoring in the Intensive Care Unit - De Backer, Daniel; Vincent, Jean-Louis (Seminars in Respiratory and Critical Care Medicine, 2020)
There has been considerable development in the field of noninvasive hemodynamic monitoring in recent years. Multiple devices have been proposed to assess blood pressure, cardiac output, and tissue perfusion. All have their own advantages and disadvantages and selection should be based on individual patient requirements and disease severity and adjusted according to ongoing patient evolution.
Keywords: microcirculation; pulse wave analysis; echocardiography; blood lactate